اُردو میں تحقیق ِ منسوبات کی رِوایت - Muhammad Yousaf Chuahan (Khayaban - خیابان, 2022)
ABSTRACT: Tehqeeq-e-mansoobat is a branch of tehqeeq in which the problem of authorship of some book is solved on the basis of internal and external evidences. Here, literal and terminological meanings of tehqeeq-e-mansoobat are given briefly. After that, complete tradition of tehqeeq-e-mansoobat in Urdu is presented from beginning to 1920 chronologically, first time. Important work is Gosha-e-Tehqeeq-e-Mansoobat of the departmental research journal Tehqeeq Jamshoro. First mohaqqiq of tehqeeq-e-mansoobat in urdu is Allama Shibli Nomani and the last one is Dr. Arif Noshahi. Qualitatively, the work of Hafiz Mehmood Sherani, Dr. Nazir Ahmed, Dr. Ghulam Mustafa Khan and Dr. Najmul Islam is prominent. Dr. Najamul Islam is one. who worked in this respect comprehensively. He set principles of tehqeeq-e-mansoobat. His translated and extracted work is also important in this dimention.